Pengaruh Temperatur Pirolisis Terhadap Karakteristik Biochar dari Limbah Padat Agroindustri Teh - Hainur Aini; Puspita Rahayu; Alizar Ulianas; Egi Agustian; Anny Sulaswatty (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
The Gambung Tea and Kina Research Center (PPTK) produces solid waste in the form of twig/branch and tea leaf waste from the pruning process of tea plants, as well as tea fluff waste from tea processing in tea factories with considerable potential. These wastes, if processed efficiently, can be a driver of circular economy activities. The high carbon content in twig, leaf, and tea fluff waste makes the waste potential to be processed into an alternative energy source in the form of fuel through a pyrolysis process. This study aims to select the most potential waste to be processed into fuel and determine the effect of pyrolysis temperature on the characteristics of the biochar produced. The results showed that tea twig and fluff waste has a higher carbon content than tea leaf waste so that it has more potential to be processed into fuel. The quality of tea twig biochar is better than tea fluff biochar because the characteristics of tea twig biochar on average meet the requirements of good biochar according to SNI 1683 2021 compared to tea fluff biochar.